Phosphodiesterase 5/protein kinase G signal governs stemness of prostate cancer stem cells through Hippo pathway. Issue 1 (1st August 2016) - Liu, Naihua; Mei, Liu; Fan, Xueying; Tang, Chao; Ji, Xing; Hu, Xinhua; Shi, Wei; Qian, Yu; Hussain, Musaddique; Wu, Junsong; Wang, Chaojun; Lin, Shaoqiang; et al.
Highlights: PDE5/cGMP/PKG and Hippo/TAZ signals are vital to maintain stemness of prostate cancer stem cells. cGMP/PKG enhance cytosolic degradation of TAZ through activating MST. Inhibition of PDE5 targets to Hippo/TAZ pathway to reduce stemness in prostate cancer stem cells. PDE5 inhibitor is a rational approach for prevention of prostate cancer. Abstract: Cancer stem cells (CSC) are critical for initiation, metastasis, and relapse of cancers, however, the underlying mechanism governing stemness of CSC remains unknown. Herein, we have investigated the roles of phosphodiesterase 5 (PDE5) in stemness of prostate cancer cells. Both PDE5 and WW domain-containing transcription regulator protein-1 (TAZ), a core effector of Hippo pathway, are highly expressed in the PC3-derived cancer stem cells (PCSC). Either TAZ knockdown or inhibition of PDE5 activity attenuated colony formation, altered expression patterns of stem cell markers, and enhanced cisplatin cytotoxicity, resulting in attenuation of stemness in PCSC. In addition, inhibition of PDE5 activity by its specific inhibitors activates cGMP-dependent protein kinase G (PKG), which in turn induces MST/LATS kinases, resulting in cytosolic degradation of TAZ and activation of Hippo pathway. Accordingly, knockdown of TAZ almost completely abolished PDE5 inhibitor-induced attenuation in stemness in cultured PCSC, whereas knockdown of TAZ not only abolished PDE5 inhibitor-induced attenuation in stemness but also facilitated PDE5 inhibitor-induced trans-differentiation in PCSC xenografts. Together, the present study has uncovered that PDE/cGMP/PKG signal targets to Hippo/TAZ pathway in maintaining stemness of PCSC, and suggested that PDE5 inhibitors in combination with chemotherapeutic agents could effectively prevent initiation, metastasis, and relapse of prostate cancer.